2017
DOI: 10.3390/rs9030271
|View full text |Cite
|
Sign up to set email alerts
|

Human Activity Influences on Vegetation Cover Changes in Beijing, China, from 2000 to 2015

Abstract: For centuries, the rapid development of human society has already made human activity the dominant factor in the terrestrial ecosystem. As the city of greatest importance in China, the capital Beijing has experienced eco-environmental changes with unprecedented economic and population growth during the past few decades. To better understand the ecological transition and its correlations in Beijing, Landsat Thematic Mapper (TM) and Operational Land Imager (OLI) images were used to investigate vegetation coverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 56 publications
5
35
1
Order By: Relevance
“…Remarkable decline in the plant species was found in the study area during the study time. Several authors have recently reported high rates of plants species decline due to settlements and agricultural activities [66][67][68][69], which was intensified by population growth and rapid urbanization [70,71].…”
Section: Overall Landuse-landcover (Lulc) Changesmentioning
confidence: 99%
“…Remarkable decline in the plant species was found in the study area during the study time. Several authors have recently reported high rates of plants species decline due to settlements and agricultural activities [66][67][68][69], which was intensified by population growth and rapid urbanization [70,71].…”
Section: Overall Landuse-landcover (Lulc) Changesmentioning
confidence: 99%
“…Increases in irrigation, grassland restoration, and conservation, and agricultural production in Inner Mongolia may have also contributed to the NDVI greening in these farmlands [65,66]. Jiang et al [67] confirmed based on an analysis of the fractional vegetation coverage (FVC) in Beijing, China, that human activities have large impacts on the FVC change and some socioeconomic influences (e.g., population growth, gross domestic product) on the FVC are highly spatially heterogeneous. Population pressure could cause vegetation browning, especially in developing countries, whereas economic and agriculture vitality could potentially exert significant positive effects on vegetation greening (see for example, [25]).…”
Section: Uncertainties In the Attribution Of Observed Ndvi Changesmentioning
confidence: 99%
“…The effect of tourists and visitors on the sand dunes can be distinguished from changes caused by vegetation cover. Vegetation cover is one of the most important indices to evaluate the conditions of the ecosystem and anthropogenic activities (Jiang et al, 2017). In order to prevent movement of dunes, during 1985-2002 in the most vulnerable coastal zones from Nida to Juodkrante (see Figure 1), reeds were planted in the shore area.…”
Section: Discussionmentioning
confidence: 99%